2009
DOI: 10.1186/bf03352903
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave splitting analysis of the upper mantle at the Niigata-Kobe Tectonic Zone with the data of the Joint Seismic Observations at NKTZ

Abstract: We conducted seismic observations with a spatially high density seismic network at the Niigata-Kobe Tectonic Zone, central Japan. The seismic network was used for the analysis of shear-wave splitting. Large lateral variations were found in the polarization direction data: the northern part of the research area yields polarization directions of NW-SE (Region A), the central part of the research area with the polarization direction of NNE-SSW (Region B), the eastern part of the research area with the polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The Japanese University Group of the Joint Seismic Observations at NKTZ started seismic observations around the Atotsugawa fault zone, north central Japan, from 2004 (The Japanese University Group of the Joint Seismic Observations at NKTZ, 2005). Iidaka et al (2009) confirmed strong anisotropy in the mantle wedge beneath the NKTZ from many shear wave splitting data obtained by this dense network.…”
Section: Introductionsupporting
confidence: 55%
“…The Japanese University Group of the Joint Seismic Observations at NKTZ started seismic observations around the Atotsugawa fault zone, north central Japan, from 2004 (The Japanese University Group of the Joint Seismic Observations at NKTZ, 2005). Iidaka et al (2009) confirmed strong anisotropy in the mantle wedge beneath the NKTZ from many shear wave splitting data obtained by this dense network.…”
Section: Introductionsupporting
confidence: 55%
“…Nakajima and Hasegawa (2007b) interpreted the low-velocity zone in the mantle wedge as being associated with upwelling flow induced by the subduction of the Philippine Sea slab. Iidaka et al (2009) investigated shear-wave splitting in central Japan and demonstrated the existence of mantle anisotropy in the N-S direction beneath the Atotsugawa fault. They attributed their observations to a preferred orientation of olivine caused by mantle return flow induced by the subduction of the Philippine Sea slab or to the alignment of melt-filled cracks in the return flow, supporting the existence of upwelling flow in the mantle.…”
Section: Deep Origin Of Fluids In the Lower Crustmentioning
confidence: 99%
“…Other groups in the Joint Seismic Observations at the NKTZ are studying seismicity, seismic tomography (Nakajima and Hasegawa, 2007), source mechanism, reflection and scattering studies, shear-wave splitting (Iidaka et al, 2009), low-frequency earthquake, and attenuation structure using data obtained by this project. The results of these analyses will contribute greatly to reveal the mechanisms of inland earthquakes.…”
Section: Introductionmentioning
confidence: 99%